My Best Friend's Boyfriend - Noonan, Rosalind (New York Parachute Press Book, 2005)
`Grease is the word' in this Sweet Sixteen story! Mary-Kate and Ashley are working on a school production of Grease, but it's tricky: the sets get ruined, the costumes need to be redone and one of the leading actors is having trouble with the script!
Include Illustrations
Keywords: a